2015
DOI: 10.1080/10615806.2015.1100298
|View full text |Cite
|
Sign up to set email alerts
|

Coping as a building mechanism to explain the unique association of affect and goal motivation with changes in affective states

Abstract: Coping partially mediates the unique association of affect and goal motivation with changes in affective states of university students.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Students with stronger autonomous motivation in EFL learning are more likely to realize the value and significance of learning a foreign language, and then develop stronger positive emotions such as enjoyment and relief. These results are consistent with self-determination theory, control-value theory of academic emotions, and previous studies (Gillet et al, 2013;Pomerantz and Qin, 2014;Blouinhudon et al, 2016). Furthermore, it was noted that both the direct and mediating effect sizes of enjoyment on students' English achievement engagement were greater than those of relief enjoyment on the achievement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Students with stronger autonomous motivation in EFL learning are more likely to realize the value and significance of learning a foreign language, and then develop stronger positive emotions such as enjoyment and relief. These results are consistent with self-determination theory, control-value theory of academic emotions, and previous studies (Gillet et al, 2013;Pomerantz and Qin, 2014;Blouinhudon et al, 2016). Furthermore, it was noted that both the direct and mediating effect sizes of enjoyment on students' English achievement engagement were greater than those of relief enjoyment on the achievement.…”
Section: Discussionsupporting
confidence: 91%
“…From the perspective of control-value theory (Pekrun, 2006), academic emotions also depend on a students' achievement goals and motivation, and the stronger the motivation, the higher the positive academic emotions students will experience. Furthermore, a handful of studies have examined the relationship between autonomous motivation and emotions and found that autonomous motivation could heighten students' positive affect (Gillet et al, 2013;Blouinhudon et al, 2016). Pomerantz and Qin's (2014) longitudinal study discovered that Chinese adolescences' autonomous motivation positively predicted pleasant emotions and negatively predicted unpleasant emotions.…”
Section: The Chain Mediating Roles Of Autonomous Motivation and Posit...mentioning
confidence: 99%
“…Coping, as a form of self-regulation under stress, relates to a myriad of consequential life outcomes (for a review, see Folkman & Moskowitz, 2004). In the context of education, the use of TOC and DOC have been, respectively, associated with many positive and negative outcomes (Amiot, Blanchard, & Gaudreau, 2008;Blouin-Hudon, Gaudreau, & Gareau, 2016;Gareau, Chamandy, Kljajic, & Gaudreau, 2018;Saklofske et al, 2012;Soucy Chartier, Gaudreau, & Fecteau, 2011). Essentially, TOC has been positively linked to academic achievement, goal progress, life satisfaction, increased self-determined motivation, well-being, and increased school satisfaction.…”
mentioning
confidence: 99%
“…Our hypotheses about how goal motives and self-regulatory coping strategies would relate to saving progress were largely supported. Task-based coping is typically beneficial for goal striving (Blouin-Hudon et al, 2016; Boileau et al, 2021; Gaudreau et al, 2012; Ntoumanis et al, 2014). Accordingly, autonomous motivation for saving predicted increases in task-based coping over 6 months, which in turn were associated with more successful saving at the end of the study, supporting H1a and H3.…”
Section: Discussionmentioning
confidence: 99%